Interactions langagières d’élèves de 11-12 ans lors de la rédaction d’un récit en dyade et leur influence sur le texte - Jessy Marin; Natalie Lavoie (Recherches en Éducation)
Offering motivating and meaningful writing activities is a challenge for teachers. Since children generally enjoy interacting with their peers, why not take advantage of this interest and allow them to write in pairs. Different studies have focused on language interactions in collaborative writing situations. Nevertheless, the state of knowledge indicates that further research is needed to better understand the content of interactions from the beginning to the end of the writing process (planning, translating and reviewing) as well as their impact on written productions. The objectives of this research are: 1- to examine the quality of narratives produced in dyad by 11-12 year old pupils and to compare it with other stories produced individually by these students and 2- to describe the content of interactions students in the planning, translating and reviewing of the narrative in dyad. Thirty-three pupil dyads participated in this study (n= 66). A text written individually was compared to a text written in pairs using various criteria (storyline, vocabulary, ponctuation, syntax, spelling and grammar). During the writing in pairs, students were filmed and interventions were organized into two categories (interventions concerning the text and other interventions). This project provides new insights into the benefits of using dyad writing to develop and improve pupils' writing skills and equips teachers with guidance on how to guide and support collaborative writing